Analisis Efisiensi Kinerja Keuangan Lembaga Amil Zakat (LAZ) Rumah Zakat Indonesia dengan Metode Data Envelopment Analysis (DEA) - Sidang, Nur Khaerat (Universitas Islam Negeri Fatmawati Sukarno Bengkulu, 2021)
Poverty in Indonesia is a very difficult problem to overcome. Therefore, one of the efforts to overcome poverty is the empowerment of the potential for zakat, infaq and alms (ZIS). However, the implementation of receipt and distribution of ZIS is still not optimal. This study aims to measure the level of efficiency of the financial performance of the Zakat Management Organization (OPZ), namely the National Zakat Management Organization (LAZ). The population in this study is the national level Indonesian Zakat House for the period 2010-2019. The factors that cause the Indonesian Zakat House to experience inefficiency as well as the policies that will be carried out by the government and the Indonesian Zakat House to improve performance or better governance. The analytical tool used non-parametric quantitative methods, namely Data Envelment Analysis (DEA) with a production approach using DEAP 2.1 software. The type of data used is secondary data in the form of financial statements of the Indonesian Zakat House for the period 2010-2019. There are two variables used in this study, namely the input variable and the output variable. The input variables in this study were operational costs, personnel costs and socialization costs, and total assets, while the output variables in this study were total ZIS funds received and ZIS funds disbursement. This study uses 2 assumptions, namely Constant Return to Scale (CRS) and Variable Return to Scale (VRS). Based on the results of research carried out with the Data Envelopment Analysis (DEA) method, it was found that the performance of Rumah Zakat Indonesia experienced efficiency in 2010, 2011, 2012, 2013, 2014, 2017, 2018 and 2019, namely 100% and Rumah Zakat Indonesia experienced inefficiency, namely in 2015 amounting to 98.1% and in 2016 amounting to 99.5%. Efficiency occurs because the actual value is not the same as the target value set by the DEA.